The Influence of Price, Brand Image and Business Location on Consumer Buying Interest a Case Study at UD. Gait Sun Tripe Surgery - Alda Nur Sa'adah; M.Imam Syairozi; Nurul Badriyah (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2024)
Consumer buying interest is something related to a consumer's plan to buy a particular product. Many factors affect consumer buying interest in a product such as: price, completeness of the product and location. The type of research used in this study is quantitative. The population in this study is UD consumers. Sumber Makmur. and the sample used in this study was 100 consumers. From the results of the t-test, it was obtained that there was a partially significant influence between the price variable (X1), product completeness (X2) and location (X3) on consumer buying interest in UD. Sumber Makmur.. Independent variables of price (X1), product completeness (X2) location (X3) have a simultaneous influence on consumer buying interest. This can be proven by the value of Fcal ˃ Ftable with a significant level of less than 0.05, which is 0.000. From the multiple linear regression equation, the result of the price variable (X1) = 0.341 is greater than the other variable. So it can be concluded that price (X1) is the most dominant variable that affects consumer buying interest (Y) in UD. Sumber Makmur.